The Adrenergic System in Plastic and Reconstructive Surgery: Physiology and Clinical Considerations. Issue 4 (October 2021) - Fahy, Evan J.; Griffin, Michelle; Lavin, Christopher; Abbas, Darren; Longaker, Michael T.; Wan, Derrick
Abstract : Abstract: The primary organ systems and tissues concerning plastic and reconstructive surgery include the integument, vasculature, subcutis, and peripheral nerves, because these may individually or collectively be injured requiring reconstruction, or indeed be used in reconstruction themselves through grafts, flaps, or anastomoses. Adrenergic receptors are present throughout these anatomic components on the vasculature, adipose, platelets, immune cells, keratinocytes, melanocytes, fibroblasts, peripheral nerves, and tendons. Herein, the influence of adrenergic signaling on the physiology of anatomic components related to plastic surgery is discussed, along with clinical considerations of this systems involvement in procedures, such as free flap reconstruction, skin grafting, fat grafting, and other areas relevant to plastic and reconstructive surgery. Current evidence as well as potential for further investigation is discussed.